Understanding dce - Rosenberry, Ward.; Kenney, David; Fisher, Gerry ([S.l.] : O'Reilly Media, 1992)
Understanding DCE is a technical and conceptual overview of OSF's Distributed Computing Environment (DCE) for programmers, technical managers, and marketing and sales people. Unlike many O'Reilly & Associates books, Understanding DCE has no hands-on programming elements. Instead, the book focuses on how DCE can be used to accomplish typical programming tasks and provides explanations to help the reader understand all the parts of DCE. Contents include: Purpose and goals of the Distributed Computing Environment. Definition of a cell. Distributing applications using RPC. Improving program performance using threads. Protecting resources using the security service. Locating network resources using the directory (name) service. Synchronizing network time using the time service. Sharing and replicating files through the distributed file system. Design and implementation considerations in writing distributed applications. Getting started as a DCE administrator. Determining your cell's boundaries. Initial choices in configuration and administrative responsibilities. Scenarios for security policies. Considerations for breaking up or replicating services across multiple hosts. Sample DCE application. Answers to commonly asked DCE questions. Finding an external time provider. Registering a cell's DNS or X.500 address.